The Theory and Practice of Zen Buddhism: A Festschrift in Honor of Steven Heine - Prebish, Charles S.; Ng, On-cho (Chinese Culture, Globality, Connectivity and Modernity, 2022)
Part I: Zen Roots -- Chapter 1. Searching for the histrorical bodhidharma in goblet words (John A. Tucker) -- Chapter 2. Chan and the routinazation of charisma in chinese buddhism (Mario Poceski).-Chapter 3. The platform sūtra and its role in chinese zen buddhism (Morten Schlütter) -- Chapter 4. Eloquence and silence: how dōgen’s dharma match with vimalakīrti turns out (Dale S. Wright).-Chapter 5. A tale of two prefaces: the role of yang yi in the creation of song chan identity (Albert Welter) -- Chapter 6. The relationship of dōgen’s vision of nature with his practice of devotion and faith (Taigen Dan Leighton) -- Chapter 7. Theorizing the chan-confician encounter in late imperial china: the chinese cultural habitus and the buddhist doxa (On-Cho Ng) -- Part II: Zen Branches -- Chapter 8. The zen explosion in america: from before the pre-boomers to after the zoomers (Charles S. Prebish) -- Chapter 9. The role of zazen in D. T. Suzuki’s Zen (Richard M. Jaffe) -- Chapter 10. Zen and the art of resistance (James Mark Shields) -- Chapter 11. Sōtō zen women’s wisdom in practice (Paula K. R. Arai) -- Chapter 12. “Can you hear the great sound of the holy footsteps?”A case study of the 650th death anniversary of Gasan Jōseki (Michaela Mross) -- Chapter 13. To tame an ox or to catch a fish: a zen reading of the old man and the sea (Pamela D. Winfield) -- Chapter 14. Steven heine on the religio-aestthetic dimension of zen buddhism (Steven Odin) -- Chapter 15. Existential dimesions of zen buiddhism: steven heine on dōgen, heidigger, and bob dylan (Jin Y. Park).